JCLexT: A Java Tool for Compiling Finite-State Transducers from Full-Form Lexicons - Alencar, Leonel F. de; Costa, Philipp B.; França, Mardonio J. C.; Ewart, Alexander; Andrade, Katiuscia M.; Andrade, Rossana M. C. (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL), 2015)
JCLexT is a compiler of finite-state transducers from full-form lexicons, this tool seems to be the first Java implementation of such functionality. A comparison between JCLexT and Foma was performed based on extensive data from Portuguese. The main disadvantage of JCLexT is the slower compilation time, in comparison to Foma. However, this is negated by the fact that a large transducer compiled with JCLexT was shown to be 8.6% smaller than the Foma created counterpart.